Bis-Anagostic Structures in N,N’-Chelate Ligand Complexes of Palladium(II) - Sajjad MA; Schwerdtfeger P; Cai Y; Waters JM; Harrison JA; Nielson AJ (Wiley-VCH Verlag, 2022)
Reaction of N,N’-dibenzylidene-2,2-dimethylpropylenediamine with Pd(OAc)2 produces essentially one product which NMR spectroscopy indicates has a bis-anagostic structure. A density functional theory (DFT) calculation shows that in the square planar structure, both aromatic rings lie above the coordination plane with close approaches of two ortho-C−H bond hydrogens to both the Pd centre and the two acetato ligand coordinating oxygen atoms. N,N’-dibenzylideneethylenediamine reacts with Pd(OAc)2 similarly where a bis-anagostic structure is indicated by NMR spectroscopy and a DFT calculation shows an energy preference for an above plane positioning of the two aromatic rings. N,N,N’,N’-tetrabenzylethylenediamine reacts with Pd(OAc)2 to give a structure which X-ray crystallography shows two benzyl phenyl groups lie above and below the coordination plane respectively.
Keywords: bis-Anagostic interactions; C-H bond activation; Cyclometallation reactions; Palladium